Law Enforcement Against Trafficking in Persons: A Case Study of the Banda Aceh Class I Immigration Office - Muhammad Andalas Mursyid; Amrullah Amrullah; T. Surya Reza (MAQASIDI: Jurnal Syariah dan Hukum, 2026)
This study examines the effectiveness of law enforcement against human trafficking by the Banda Aceh Class I Immigration Office through a multidimensional preventive approach. Using a qualitative method with a normative-empirical approach, this study found that suspected TPPO cases in Aceh increased from 3 cases in 2023 to 10 cases by August 2025, driven by factors such as poverty, low migration literacy, and promises of high wages via social media. Key law enforcement strategies implemented include strict verification of travel documents, which successfully prevented the issuance of 473 passports linked to potential human trafficking throughout 2025, as well as the establishment of 21 Immigration-Assisted Villages and PORA Teams for the monitoring of foreign nationals. Although protective measures have been provided through restitution and rehabilitation in accordance with human rights standards, their implementation remains hampered by a lack of interagency coordination, passport bribery practices, and technological limitations in remote areas. This study recommends the need for a transformation in working methods toward early prediction by integrating biometric facial and fingerprint recognition technology, strengthening cross-sectoral coordination, and implementing comprehensive policies to address the root causes of poverty in rural Aceh in order to protect prospective migrant workers sustainably.